Pemenuhan Hak Dasar Anak Dalam Situasi Darurat Covid-19 di Kabupaten Jember - Dina Tsalist Wildana; Fanny Tanuwijaya; Sapti Prihatmini; Jauhari Zakky Anas (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
The Covid-19 pandemic, which has become a global epidemic, requires the implementation of health protocols in order to prevent its spread, creating its own social problems, especially for the growth and development of children, so that they are the most affected. This study uses empirical juridical methods and uses a conceptual approach. The results of this study indicate that the problem of fulfilling children's rights during the pandemic is still a priority scale program by the government in Jember Regency which must be resolved immediately, especially in terms of health and education. In the context of health, children still have not received vaccination facilities. On the other hand, online children's education is also not optimal due to limited interaction between teachers and students. This research also formulates recommendations for formulating precise policies in terms of mainstreaming the fulfillment of rights to children during the Covid-19 pandemic, especially in Jember Regency, establishing an accountable and accurate information system regarding the distribution of children affected by the Covid-19 pandemic, and making new breakthroughs related to mechanisms. education, health and the environment in favor of the fulfillment of children's rights